The effect of ambiguity on price formation and trading behavior in financial markets - Wenhui Li; Peter Ockenfels; Christian Wilde (Leibniz Institute for Financial Research SAFE, 2021)
This paper sets up an experimental asset market in the laboratory to investigate the effects of ambiguity on price formation and trading behavior in financial markets. The obtained trading data is used to analyze the effect of ambiguity on various market outcomes (the price level, volatility, trading activity, market liquidity, and the degree of speculative trading) and to test the quality of popular empirical market-based measures for the degree of ambiguity. We find that ambiguity decreases market prices and trading activity; ambiguity leads to lower market liquidity through wider bid-ask spreads; and ambiguity leads to less speculative trading. We also find that popular market-based measures of ambiguity used in the empirical literature do not seem to correctly capture the true degree of ambiguity.
Keywords: D81; G10; 330; ambiguity; financial market; market price; volatility; trading activity; bidask spread; market-based measure of ambiguity; laboratory experiment